Analysis of Statistical Learning Outcomes with Online and Offline Learning Methods - Kurniawan, Indra; Rahadyan, Andri (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
This study analyses what factors make online learning outcomes better than offline. It is crucial to know whether there are other supporting factors or factors from the students' abilities. The method used in this research is descriptive research using a qualitative approach with six research subjects. The selection of subjects in this study was by purposive sampling. Collecting data in this study using task-based interviews, namely: (1) selecting research subjects; (2) determining the time of data collection; (3) carrying out data collection; (4) analysing data; (5) comparing the results of online and offline data collection; and (6) conclude the results of the analysis. The results of the analysis of this study are that the application of online learning methods and offline methods has little effect on material understanding, enthusiasm and independence in learning. The things that need attention are not the learning method, but how we can foster a good and consistent spirit for education, especially for students with medium and low abilities, it is vital to increase the excitement for learning in all learning methods because, with a consistent enthusiasm for learning, students will be happy. And active when participating in class learning both with online and offline modes.